Docosahexaenoic Acid (DHA) Down-regulates Cellular, and Exosomal Overexpressed Mammalian Target of Rapamycin (mTOR) in Breast Cancer Cells Under Hypoxic Condition - Sepideh Maralbashi; Farhad Salari; Cynthia Aslan; Houman Kahroba; Milad Asadi; Zahra Asghari; Tohid Kazemi (ImmunoAnalysis)
Background: The omega-3 long-chain polyunsaturated fatty acid, docosahexaenoic acid (DHA), shows anti-proliferative effects in cancer cell lines and animal models. The mammalian target of rapamycin (mTOR) is one of the regulators for the proliferation and survival of cancer cells. This study focused on the effect of DHA on cellular and exosomal expression of mTOR and related tumor-suppressor microRNAs (miRs) in triple-positive (BT-474) and triple-negative (MDA-MB-231) breast cancer (BC) cell lines. Methods: BT-474 and MDA-MB-231 cells were treated with 100 μM DHA under hypoxic and normoxic conditions for 24 hours. The exosomes were isolated by ultracentrifuge and determined by electron microscopy and CD9, CD63, and CD81 immunoblotting. cDNAs from cellular and exosomal total RNA were used for evaluation of the expression of mTOR and related tumor-suppressor miRs, miR-101 and miR-214, by quantitative real-time PCR. Results: We demonstrated that DHA significantly decreased cellular and exosomal expression of mTOR in both normoxic and hypoxic conditions for both cell lines. Consistently, DHA caused significantly increased expression of miR-214 in all treated groups. However, altered expression of miR-101 showed different patterns in cells and exosomes. Conclusion: According to the beneficial effect of DHA in decreasing the expression of a master regulator for the proliferation of cancer cells, mTOR, in part by increased expression of miR-214, it could be used as a supplementary therapy in BC treatment. Also, miRNA replacement therapy would be useful by suppressing the expression of mTOR in BC treatment.